Poderti, Alicia. Diccionario del peronismo. Buenos Aires, Editorial Biblos, 2010. 252 páginas. ISBN 978-950-7867-97-2. - Günther Ibach, Hermann (2012)
Fil: Günther Ibach, Hermann. Universidad Nacional de San Luis